Cognitive Behavioral Therapy in Children and Adolescents with Anxiety Disorder - Didem Behice ÖZTOP; Emel KARAKAYA (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Currently, Cognitive Behavioral Therapy (CBT) becomes one of the leading approaches in the psychotherapy. However,use of CBT in childhood psychotherapy is considerably novel. After 1990s, it has been understood that it is an effectivemethod for children and adolescents. Anxiety disorders are one of the most common problems in the field of childhoodand adolescent psychiatry. In the studies conducted, the effectiveness of CBT was demonstrated in anxiety disorders ofthe children and adolescents. Moreover, it was suggested that this effectiveness is permanent in some studies. Prioritygoal of CBT is to change inappropriate learning and thinking patterns in the children and adolescents. By “now and here”fashion, it is attempted to reveal the origin of current problems. During the process, the factors are considered, whichcause to maintain the symptoms. It is attempted to decrease signs caused to stress by improving coping skills duringtherapy. To this end, methods including observation, relaxation training, systematic desensitization, social skills training,cognitive restructuring and exposure therapy are applied in sessions by taking child’s problems into consideration. Scalesspecific to anxiety disorders are used in the assessment and follow-up. Age and development level of the child should beparticularly taken into account while using assessment tools and therapeutic modality.